1973
DOI: 10.1021/jo00950a032
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemistry of fegrifugine. I. Equilibrium between cis- and trans-(3-substituted 2-piperidyl)-2-propanones

Abstract: A facile thermal equilibration of cis-(3-methoxy-2-piperidyl)-Z-propanone and some analogous cis-(&substituted 2-piperidyI)-Z-propanones with their trans isomers is reported. The effects on the equilibrium of temperature, solvent, pH, and the size of the 3 substituent were investigated. Chemical and nmr spectral data and conformational free-energy calculations are presented to support the assignment of the trans configuration to the more stable isomer.The title compounds are intermediates in the synthesis of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1973
1973
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…-OH, trans b, Y = OH, cis c, Y = OCOCH3, trans mediate in one synthesis of the hydrangea alkaloid, febrifugine (2a),2 led to a reconsideration of the stereochemistry of the piperidine moiety of febrifugine. Baker, et at., synthesized a second intermediate (3methoxy-2-piperidyl)-2-propanone(1) and…”
mentioning
confidence: 99%
“…-OH, trans b, Y = OH, cis c, Y = OCOCH3, trans mediate in one synthesis of the hydrangea alkaloid, febrifugine (2a),2 led to a reconsideration of the stereochemistry of the piperidine moiety of febrifugine. Baker, et at., synthesized a second intermediate (3methoxy-2-piperidyl)-2-propanone(1) and…”
mentioning
confidence: 99%
“…Febrifugine (1) and isofebrifugine (2) were isolated as active principles against malaria. 1,2 The absolute configurations of 1 and 2 were revised very recently through the asymmetric total synthesis of each stereoisomer of febrifugine by Kobayashi et al 3 Isofebrifugine (2) is an isomer of febrifugine (1) (Scheme 1) which is said to isomerize by the mechanism suggested by Berkelhammer et al 4 In our experiments, the isomerization of 1 to 2 and the reverse reaction were found to readily occur in a protic solvent, such as methanol. Treatment of these compounds in methanol at 50°C for less than 12 h afforded a 1:1 mixture of each compound as judged on the basis of TLC analysis.…”
Section: Introductionmentioning
confidence: 59%
“…The recovered material contained 13% of a new glpc peak at 7.0 min (175°) in addition to 87% of the starting isomer peak. Gas chromatography-mass spectra showed that this new peak was an isomer of 9: new peak mass spectrum m/e (rel intensity) 198 (30), 167 (15), 139 (23), 111 (100), 97 (59), 84 (7); starting isomer peak mass spectrum m/e (rel intensity) 198 (12), 167 (14), 139 (32), 111 (55), 97 (100), 84 (12). On extending the reflux time to 4 hr only a 14% recovery of material which contained 21% of the new peak was possible.…”
Section: Methodsmentioning
confidence: 99%